Pozycja prawna spikera Izby Gmin - Pastuszko, Grzegorz (Polityka i Społeczeństwo, 2020)
The subject matter of this article is the institution of the Speaker in the British parliamentary system. All the remarks, set out in the article, focus on four major themes: 1) genesis of the office, 2) mechanism for election and the duration of the term of office, 3) impartiality and, 4) scope of the powers produced by legislation or created in parliamentary practice. As can be seen then, the concept of the article enables the contemporary institution of the Speaker to be portrayed including the historical background. It also enables the author to prove his main thesis, indicating that all the changes concerning this institution, which have been made over last couple of years, resulted neither in enhancing nor in weakening the parliamentary role of the Speaker as a neutral arbitrator between political parties in the UK parliament.